Issues and New Directions in Public Expenditure Management - Premchand, A. (Washington, D.C. : International Monetary Fund, 1996)
The public expenditure management system is in a state of flux. Traditional approaches of expenditure management have serious limitations in addressing current and future tasks. The new approaches toward improved expenditure management, which emphasize the creation of task-oriented agencies, performance agreements, and competitive tendering and contracting, have considerable potential in meeting the tasks. But it is essential to address the detailed operational aspects of these new approaches so that they do not contribute to a shadow government or a government that continues to be weak in regard to contracts and third-party transactions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet